Removal of fecal coliforms from sewage treatment plant tailwater through AMF-Canna indica induced bioretention cells - Fei Wang; Kemei Zhou; Dafang Fu; Rajendra Prasad Singh (Ecological Indicators, 2023)
Fecal coliform in the tailwater from sewage treatment needs to be deeply removed by chlorine disinfection, but ensuing disinfection by-products (DBPs) bring severe environmental and sanitary risks. Therefore, current work focused on whether bioretention cells can be used as an eco-friendly method to effectively remove fecal coliforms from tailwater remains to be further studied. Three saturated arbuscular mycorrhizal fungi (AMF)-Canna indica L. induced bioretention cells with anthracite of different sizes (0.5–1, 1–2, and 2–4 mm) and their control groups were designed to investigate tailwater fecal coliform removal efficiency. The AMF colonization of Glomus on Canna and its improvement effect, as well as the factors affecting the fecal coliform removal efficiency of the AMF-Canna bioretention cells, were discussed. The results revealed that AMF could successfully inoculate on Canna to form a stable symbiotic system and improve its plant height, root length, and underground biomass. The bioretention cells could remove fecal coliforms of 1.37 log to 3.73 log in the tailwater from sewage treatment (103.04–104.73 MPN/L). The removal efficiency of fecal coliforms of bioretention cells would be improved with AMF inoculation and the increase of the influent fecal coliform concentration, but the influence of hydraulic retention time (HRT) was relatively limited. Current findings proved that bioretention cells investigated in the present study had potential to further reduce the HRT and increase the influent pollution load on the premise of performing efficient fecal coliform removal.